Population pharmacokinetic modeling of GS‐441524, the active metabolite of remdesivir, in Japanese COVID‐19 patients with renal dysfunction. (18th November 2021) - Sukeishi, Asami; Itohara, Kotaro; Yonezawa, Atsushi; Sato, Yuki; Matsumura, Katsuyuki; Katada, Yoshiki; Nakagawa, Takayuki; Hamada, Satoshi; Tanabe, Naoya; Imoto, Eishi; Kai, Shinichi; Hirai, Toyohiro; et al.
Abstract: Remdesivir, a prodrug of the nucleoside analog GS‐441524, plays a key role in the treatment of coronavirus disease 2019 (COVID‐19). However, owing to limited information on clinical trials and inexperienced clinical use, there is a lack of pharmacokinetic (PK) data in patients with COVID‐19 with special characteristics. In this study, we aimed to measure serum GS‐441524 concentrations and develop a population PK (PopPK) model. Remdesivir was administered at a 200 mg loading dose on the first day followed by 100 mg from day 2, based on the package insert, in patients with an estimated glomerular filtration rate (eGFR) greater than or equal to 30 ml/min. In total, 190 concentrations from 37 Japanese patients were used in the analysis. The GS‐441524 trough concentrations were significantly higher in the eGFR less than 60 ml/min group than in the eGFR greater than or equal to 60 ml/min group. Extracorporeal membrane oxygenation in four patients hardly affected the total body clearance (CL) and volume of distribution ( V d ) of GS‐441524. A one‐compartment model described serum GS‐441524 concentration data. The CL and V d of GS‐441524 were significantly affected by eGFR readjusted by individual body surface area and age, respectively. Simulations proposed a dose regimen of 200 mg on day 1 followed by 100 mg once every 2 days from day 2 in patients with an eGFR of 30 ml/min or less. In conclusion, we successfully established a PopPK model of GS‐441524 using retrospectively obtained serum GS‐441524 concentrations in Japanese patients with COVID‐19, which would be helpful for optimal individualized therapy of remdesivir.